Renal tumors in children and adolescents (primary diagnostics based on a pilot study) - E.A. Karavaeva; T.E. Taranushenko; A.V. Morgun; M.V. Borisova; T.G. Kadricheva; T.I. Bulava; N.A. Gonchar; E.A. Guseynova (LCC «Medicine-Inform», 2021)
E.A. Karavaeva1, T.E. Taranushenko2, A.V. Morgun2, M.V. Borisova1, T.G. Kadricheva1, T.I. Bulava1, N.A. Gonchar1, E.A. Guseynova1 1Krasnoyarsk Regional Clinical Center for Maternal and Child Welfare, Krasnoyarsk, Russian Federation 2Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation Aim: to assess the rate of detection and epidemiology of renal tumors in children of the Krasnoyarsk Krai and to specify some tumor characteristics during primary diagnostics. Patients and Methods: retrospective exploratory (pilot) dynamic single-center study was conducted. A group of 46 children and adolescents with renal tumors who were admitted to the Department of Hematological Malignancies for examinations and treatment in 2011-2019. All data were obtained from hospital register. Results: renal tumors account for 6.4% of hematological malignancies first diagnosed in children. 9-year primary incidence of renal tumors in children was, on average, 0.87 per 100,000 children, alternating between the increase and decrease in the detection rate. Renal tumors rank 4th among hematological malignancies in the Krasnoyarsk Krai children. The mean age was 4.1±0.5 years. No gender differences were revealed. In a pre-hospital setting, renal tumors were suspected in 24 children (52%). The most common complaints were abdominal pains (34 patients, 74%) and enlarged abdomen (30 patients, 65%). Most renal tumors (40 out of 46) were nephroblastoma as demonstrated by histology. The distribution by prognostic risk (the likelihood of recurrence and/or other unfavorable outcome) has shown that most patients have intermediate (n=25, 54%) or high (n=19, 42%) risk. Conclusions: our findings illustrate that children with renal tumors require more attention of pediatricians in a pre-hospital setting (cancer vigilance about abdominal pains and enlarged abdomen in children) to reduce the time to diagnosis and to increase the use of renal ultrasound during checkups or in suspicious renal tumors. Keywords: nephroblastoma, Wilms tumor, renal tumors, children, epidemiology, prevalence, primary diagnostics. For citation: Karavaeva E.A., Taranushenko T.E., Morgun A.V. et al. Renal tumors in children and adolescents (primary diagnostics based on a pilot study) . Russian Journal of Woman and Child Health. 2021;4(2):162-167. DOI: 10.32364/2618-8430-2021-4-2-162-167.